2007
DOI: 10.1111/j.1742-7843.2007.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Prevents Cisplatin‐Induced Oxidative Stress in Liver and Heart Tissue of Rats

Abstract: Cisplatin is one of the most active cytotoxic agents in the treatment of cancer. High doses of cisplatin have also been known to produce hepatotoxicity, and several studies suggest that supplemental antioxidants can reduce cisplatin-induced hepatotoxicity. The present study was designed to determine the effects on the liver and heart oxidant/antioxidant system and the possible protective effects of ellagic acid on liver and heart toxicity induced by cisplatin. The control group received 0.9% saline; animals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 42 publications
(63 reference statements)
7
70
0
Order By: Relevance
“…On the other hand, the tubules and liver cells from rats in the CDDP + L-carnitine group were nearly normal in histological architecture, except for a minor desquamation of the kidney and liver epithelial cells. Similar findings were also reported by Yuce et al [44] and Tarladacalisir et al [6], demonstrating the structural changes in the kidney and liver tissues of CDDP-treated animals and its turn back by different agents.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the tubules and liver cells from rats in the CDDP + L-carnitine group were nearly normal in histological architecture, except for a minor desquamation of the kidney and liver epithelial cells. Similar findings were also reported by Yuce et al [44] and Tarladacalisir et al [6], demonstrating the structural changes in the kidney and liver tissues of CDDP-treated animals and its turn back by different agents.…”
Section: Discussionsupporting
confidence: 79%
“…It was suggested that HES has positive effects on SOD, CAT and GSH-Px activities and has protective effects against oxidative stress in rat brain 76 . In another study, it has been demonstrated that EA enhanced increased tissue SOD, CAT and GSH-Px activities 77 . According to our results, it has been detected that SOD, CAT and GSH-Px activities increased in EA and HES groups compared to ischemia and I/R groups.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that different natural antioxidants such as vitamin C, vitamin E, ellagic acid, nigella sativa, lycopen, caffeic acid phenethyl ester prevent cisplatin-induced toxicity. 13,28,[32][33][34][35] In this study, we investigated the effects of the natural antioxidants GSE and OOEO in cisplatin-treated rats by microscopic examination and biochemical assays.…”
Section: Discussionmentioning
confidence: 99%